A kids book about : gratitude - Kenyon, Ben ([Portland] : A Kids Book About, Inc., 2019)
This book explores what it means to be grateful. Not just for the big things like birthday parties and iPhones, but the small things like dinner, a cozy bed, and a sunny day. This book doesn't teach kids how to pretend like everything is always ok, but to change their perspective to live bold, influential, and authentic lives.
3-6
Keywords: Gratitude -- Juvenile literature; Gratitude in children -- Juvenile literature